Students’ Use of Smartphone Apps in Higher Education Institutions - Hajjaj, Amir (South Asian Journal of Social Sciences and Humanities, 2025)
This study explores the Higher Education (HE) learners’ attitude toward using the Smartphone One Lesson Apps (SOLA) as a proactive browser for the topics and skills of the next lesson in the class rooms of Higher Education Institutes (HEIs). A sample of Omani students from different sections of the Foundation Program of Information Technology (FPIT) of the Foundation Program Level (FPL) at the University of Technology and Applied Science (UTAS-Salalah in Oman) had been encouraged to complete the designed survey for this purpose using a 5-points likert-scale. The collected data was formatted and analyzed using SPSS. The outcomes showed that the respondents mostly used the SOLA for proactive review and practice, which led to well prepared for the next lesson’s objectives and skills, thus improving the FPIT system and the desired skills as well. Moreover, the respondents in general offered positive attitudes toward the SOLA. Furthermore, the results propose motivated and ambitious inferences for utilizing SOLA applications in FPIT and other courses in the HEIs